Strengthening the Marketing Communication Through Product Design and Packaging - Okki Trinanda; Astri Yuza Sari (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2019)
This Community Service aims to improve the Marketing Communication of Tenun Mulia groups of Solok Regency, by (1) strengthening the skills on creating packaging, and (2) product design training. Packaging is one of the weak points of the Tenun Mulia group. Good packaging is needed to support the relatively expensive products they produce. Furthermore, Product Design is intended to provide skills to develop weaving patterns / motifs for weavers. The results of this activity are: (1) improvement of skills in producing packaging, as well as the emergence of five new MSMEs in the field of packaging production, and (2) new motifs named "Markisa Babijo Ameh".